Long‐term consequences of juvenile vulvar lichen sclerosus: A cohort study of adults with a histologically confirmed diagnosis in childhood or adolescence - Beth Morrel; Irene A. M. van derAvoort; Patricia C. Ewing‐Graham; Jeffrey Damman; Renske Schappin; Kelly N. vanZeijl; Quirinus J. M. Voorham; participants in the Steering Group‐JVLS; Marianne J. tenKate‐Booij; Curt W. Burger; Suzanne G. M. A. Pasmans (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Vulvar lichen sclerosus (VLS) occurs in at least one in 900 girls. There is limited knowledge as to what extent the disease persists in adulthood and what the repercussions in adulthood may be. The aim of this study is to evaluate the long‐term consequences of VLS diagnosed in childhood or adolescence. Material and methods The population of females histologically diagnosed with VLS in childhood or adolescence in the Netherlands between 1991 and 2015 was identified through the national pathology database. Histological specimens were retrieved and re‐evaluated. Potential participants for whom the diagnosis was reconfirmed and who are now adults, were then traced and surveyed. Descriptive statistics were calculated and compared with the literature. Main outcome measures are the demographics of the cohort, their scores on standardized quality of life (QoL) and sexuality questionnaires and answers to additional questions regarding patients’ experience with the disease. The questionnaires used were the Dermatology Life Quality Index (DLQI), the Skindex‐29, the Female Sexual Function Index (FSFI) and the Female Sexual Distress Scale‐Revised (FSDS‐R). Secondary outcome measures include obstetric history and histological features found in the original tissue specimens. Results A total of 81 women participated, median age 29.0 years, median follow‐up from childhood diagnosis 19.5 years. Both QoL and sexuality were somewhat affected in 51.9% of cases. Less than half (45%) reported having regular check‐ups. Forty‐five (56%) reported symptoms within the past year; of those with symptoms, 14 (31%) were not under surveillance. Cesarean section rate (14.5%) was comparable to the general population, and there were more high‐grade obstetric anal sphincter injuries with vaginal deliveries than expected. Sixteen respondents (20%) were not aware of the childhood diagnosis prior to this study. Conclusions Symptoms due to VLS are reported by most adults diagnosed as juveniles. QoL and sexuality are affected and correlate to recent symptoms. VLS as a juvenile does not preclude a vaginal delivery. Women diagnosed with VLS in childhood or adolescence are often lost to follow‐up.